Efisiensi Bio-Porta Tank (Bacterial Portable Septic Tank) Terhadap Sanitasi Perumahan di Desa Kubang Jaya Kecamatan Tambang Kabupaten Kampar - M. Imam Arifandy; Darusman Darusman; Yefni Yefni; Muhammad Soim; Titi Antin; Kodarni Kodarni (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to examine the efficiency of Bio-Porta tanks created by a group of residential communities in Kubang Jaya Village and Alumni of the Engineering Faculty at the University of Riau, comparing it with conventional septic tanks. The study employs a mixed methods approach, which is a combination of quantitative and qualitative techniques. This approach is chosen to provide a more holistic and in-depth understanding of the efficiency of the Bio-Porta Tank in sanitation in Kubang Jaya Village, Tambang District, Kampar Regency. The high groundwater level around the septic tanks in Kubang Jaya Village poses a major challenge. Kubang Jaya Village seeks to address septic waste issues by adopting an innovative solution in the form of the Bioporta Tank. From the research results regarding the efficiency of the Bio-Porta Tank (bacterial portable septic tank) in residential sanitation in Kubang Jaya Village, Tambang District, Kampar Regency, the efficiency of the Bio-Porta is higher compared to conventional septic tanks. This can be observed in terms of cost difference and effectiveness in waste treatment. This difference is reflected in a cost difference of Rp. 1,647,300.